Sex differences in the relationships between 24-h rest-activity patterns and plasma markers of Alzheimer’s disease pathology - Maxime Van Egroo; Elise Beckers; Nicholas J. Ashton; Kaj Blennow; Henrik Zetterberg; Heidi I. L. Jacobs (Alzheimer’s Research & Therapy)
Abstract Background Although separate lines of research indicated a moderating role of sex in both sleep-wake disruption and in the interindividual vulnerability to Alzheimer’s disease (AD)-related processes, the quantification of sex differences in the interplay between sleep-wake dysregulation and AD pathology remains critically overlooked. Here, we examined sex-specific associations between circadian rest-activity patterns and AD-related pathophysiological processes across the adult lifespan. Methods Ninety-two cognitively unimpaired adults (mean age = 59.85 ± 13.77 years, range = 30–85, 47 females) underwent 10 days of actigraphic recordings, and blood drawing. Standard non-parametric indices of 24-h rest-activity rhythm fragmentation (intradaily variability, IV) and stability (interdaily stability, IS) were extracted from actigraphy data using the GGIR package. Plasma concentrations of neurofilament light chain (NfL), glial fibrillary acidic protein (GFAP), amyloid-β42/40 (Aβ42/40), total tau, and tau phosphorylated at threonine 181 (p-tau181) or threonine 231 (p-tau231) were measured using Single molecule array technology. Multiple linear regression models were adjusted for age, sex, education, body mass index, and actigraphic recording duration. Results Higher IV, indicating worse 24-h rest-activity rhythm fragmentation, was associated with elevated levels of plasma NfL (t(85) = 4.26, P < 0.0001), GFAP (t(85) = 2.49, P = 0.01), and at trend level with lower Aβ42/40 ratio values (t(85) = -1.95, P = 0.054). Lower IS, reflecting less day-to-day stability in the 24-h rest-activity rhythm, was linked to elevated levels of plasma NfL (t(85) = -2.24, P = 0.03), but not with the other plasma biomarkers. Importantly, interaction models demonstrated that male participants were driving the observed relationships between IV and plasma NfL (t(84) = 4.05, P < 0.001) or GFAP (t(84) = 3.60, P < 0.001), but also revealed a male vulnerability in models testing interactions with p-tau181 (IV: t(76) = 3.71, P < 0.001; IS: t(76) = -3.30, P = 0.001) and p-tau231 (IV: t(82) = 3.28, P = 0.002). Sensitivity analyses further showed that accounting for potential confounding factors such as APOE genotype, depression, and self-reported symptoms of possible sleep apnea did not modify the observed relationships. Conclusions These findings suggest that the association between disrupted circadian rest-activity patterns and AD pathophysiological processes may be more evident in cognitively unimpaired males. Our results contribute to the precision medicine approach, and they have clinical implications for improved early detection and selection of at-risk individuals to be enrolled in preventive interventions.